2013
DOI: 10.1371/journal.pone.0062030
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Exposure to Multilingualism: New Evidence to Support Cognitive Reserve Hypothesis

Abstract: ObjectiveInvestigate the protective effect of multilingualism on cognition in seniors.MethodsAs part of the MemoVie study conducted on 232 non-demented volunteers aged 65 and more, neurogeriatric and neuropsychological evaluations were performed. Participants were classified as presenting either cognitive impairment without dementia (CIND) or being free of any cognitive impairment (CIND-free). Language practices, socio-demographic data and lifestyle habits were recorded. In this retrospective nested case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 30 publications
8
76
0
2
Order By: Relevance
“…Similar results were reported in cognitive aging (n=232) (Perquin et al, 2013) and dementia (n=134) (Woumans et al, 2014). Thirdly, in large parts of the world bilingualism is the rule rather than exception.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Similar results were reported in cognitive aging (n=232) (Perquin et al, 2013) and dementia (n=134) (Woumans et al, 2014). Thirdly, in large parts of the world bilingualism is the rule rather than exception.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…They proposed for the first time that the more languages old people spoke on regular basis, the higher their cognitive levels would be [21]. It is known as the cumulative effect of languages, which is consistent with the results of Luxembourg's study that mastering one more language would increase the probability of protection against cognitive impairment by more than four times (of course, a threshold existed) and the earlier they became multilingual, the greater the protection would be [25]. It is a pity that this research didn't involve monolinguals, which makes impossible the comparison between monlolinguals and bilinguals or multilinguals (people speaking more than two languages).…”
Section: Bilingualism Contributing To Better Cognitive Ability In Heasupporting
confidence: 54%
“…One study had a 14% follow-up rate and did not compare those who dropped out and those who did not [12]. The other was cross-sectional and found being multilingual rather than bilingual was protective, giving an odds ratio of 0·3 for cognitive impairment (95% Confidence Interval 0·10-0·92) after adjustment for education and age [13]. Both studies found that knowing and using more than two languages seems to confer a cognitive advantage and multi-lingualism may differ from bilingualism but there is not enough evidence as yet to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%